Regulation of intercellular coupling in acute and chronic heart disease - J.E. Saffitz (Brazilian Journal of Medical and Biological Research, 2000)
Effective pump function of the heart depends on the precise control of spatial and temporal patterns of electrical activation. Accordingly, the distribution and function of gap junction channels are important determinants of the conduction properties of myocardium and undoubtedly play other roles in intercellular communication crucial to normal cardiac function. Recent advances have begun to elucidate mechanisms by which the heart regulates intercellular electrical coupling at gap junctions in response to stress or injury. Although responses to increased load or injury are generally adaptive in nature, remodeling of intercellular junctions under conditions of severe stress creates anatomic substrates conducive to the development of lethal ventricular arrhythmias. Potential mechanisms controlling the level of intercellular communication in the heart include regulation of connexin turnover dynamics and phosphorylation.